2015
DOI: 10.1007/s00262-015-1659-7
|View full text |Cite
|
Sign up to set email alerts
|

Strengthened tumor antigen immune recognition by inclusion of a recombinant Eimeria antigen in therapeutic cancer vaccination

Abstract: The need for novel, effective adjuvants that are capable of eliciting stronger cellular and humoral adaptive immune responses to antigenic targets is well understood in the vaccine development field. Unfortunately, many adjuvants investigated thus far are either too toxic for human application or too weak to induce a substantial response against difficult antigens, such as tumor-associated antigens (TAAs). In spite of this trend, clinical investigations of recombinant Eimeria antigen (rEA) have revealed this p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
3
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
3
1

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 51 publications
0
3
0
Order By: Relevance
“…TLR activation can promote a robust innate immune response and produce anti-tumor responses. For example, TLR agonists can increase tumor antigen-specific cytotoxic T cell killing, 14 - 16 lead to anti-tumor Th1 polarization, 17 , 18 and boost anti-PD-1 adaptive immunity. 19 , 20 There has been considerable interest in TLR9, a receptor that recognizes unmethylated CpG oligodeoxynucleotides (ODN) commonly found in bacterial and viral genomes.…”
Section: Introductionmentioning
confidence: 99%
“…TLR activation can promote a robust innate immune response and produce anti-tumor responses. For example, TLR agonists can increase tumor antigen-specific cytotoxic T cell killing, 14 - 16 lead to anti-tumor Th1 polarization, 17 , 18 and boost anti-PD-1 adaptive immunity. 19 , 20 There has been considerable interest in TLR9, a receptor that recognizes unmethylated CpG oligodeoxynucleotides (ODN) commonly found in bacterial and viral genomes.…”
Section: Introductionmentioning
confidence: 99%
“…Indeed, TAAs are overexpressed in tumor cells but often fail to induce sufficient immune responses. Thus, one of the main purpose in the cancer vaccine fields is to enhance TAA-specific cellular immune responses via allowing the delivery of different TAAs that can be able to stimulate the effective antitumor immunity (3,4). Many researches have confirmed that the infiltration of T cells into tumor microenvironment is associated with increase survival without recurrence in patients.…”
Section: Introductionmentioning
confidence: 99%
“…Ad5-based vaccines are attractive for a multitude of reasons, including their broad human cell tropism, relative ease of manufacturing for scaled production, and low potential for adverse side effects (1). Additionally, numerous studies have demonstrated the tremendous ability of Ad5-based vaccines to create robust, transgene-specific cell-mediated immunity against antigens derived from pathogens, such as HIV (2)(3)(4)(5)(6)(7)(8), the malaria parasite (9,10), and Mycobacterium tuberculosis (11,12), as well as many tumor-associated antigens (13)(14)(15)(16)(17). Although the advantages of these vaccines are abundant, there has been some hesitation toward their practical use due to the high prevalence of preexisting Ad5 immunity in the human population (18)(19)(20).…”
mentioning
confidence: 99%